Pharmacological Approach of Pistacia Vera Fruit to Assess Learning and Memory Potential in Chemically-Induced Memory Impairment in Mice - Singh, Satyam; Dharamveer; Kulshreshtha, Mayank (Central Nervous System Agents in Medicinal Chemistry, 2019)
Objective: The present study was designed to investigate the potential of Pistacia vera (P. vera) fruits in experimental memory impairments in mice. Material & Methods: Memory impairment was induced in Swiss Albino mice by scopolamine (0.4mg mg/kg. i.p). Animals were divided into five separate groups of six animals each, positive control group received carboxy methyl cellulose (CMC) as vehicle, negative control group received scopolamine with vehicle, and standard group received donepezil (5mg/kg i.p) with Scopolamine. Ethanolic extract of P. vera (EEPV) at doses of 200mg/kg & 400mg/kg p.o were administered to group test1 & test 2 respectively along with scopolamine. Elevated plus maze (EPM), passive avoidance paradigms and morris water maze (MWM) were used as exteroceptive behavioral models to access learning and memory activity. Transfer latency, step down latency and escape latency parameters were evaluated plus maze, passive avoidance paradigm, morris water maze. Thereafter lipid peroxidation test, glutathione level and catalase activities were estimated in homogenized brain of mice. Results: Pretreatment of mice with EEPV (200mg/kg & 400mg/kg) significantly reduced scopolamine induced amnesia. The obtained data clearly revealed that there was increase in escape latency in MWM and also increase in step down latency in passive avoidance paradigm. Transfer latencey was found to be decrease in EPM and biochemical. Parameters were clearly satisfied the data as compared to negative control group which was indicative of cognitive improvement. Conclusion: P. vera fruit extract demonstrated to improve cognitive process by enhancing memory in different experimental paradigm such as EPM, passive avoidance and MWM when administered orally. Hence it would be worthwhile to explore the potential of this plant in the management of memory disorders.
Keywords: Pistacia vera